Ultrafast high-temperature sintering of bulk oxides. (1st March 2021) - Guo, Rui-Fen; Mao, Hai-Rong; Zhao, Zhi-Tao; Shen, Ping
Abstract: Conventional ceramic sintering often requires high temperatures and hours of duration to achieve near full density. Herein, we adopted an innovative ultrafast high-temperature sintering (UHS) technique to densify several representative bulk oxides within an isothermal duration of 30 s and a total sintering period of several minutes, and revealed the relationship between ceramic structures and processing parameters. These achievements demonstrate the great potential of the UHS technique in the rapid densification of ceramics. Moreover, this flexible technique is expected to accelerate the material screening rate and facilitate the development of novel materials. Graphical abstract: Image, graphical abstract